2023
DOI: 10.3390/nu15020322
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Zinc Intake, Serum Zinc Level and Multiple Comorbidities in Older Adults

Abstract: Zinc is one of the essential micronutrients in the geriatric population, but the importance of zinc status and dietary zinc intake has been poorly characterized. We aimed to explore the relationships among dietary zinc intake, serum zinc concentrations and multimorbidity in a cross-sectional study of 300 employees of Electric Generating Authority of Thailand aged ≥ 60 years. Comprehensive questionnaires were completed, and clinical and laboratory assessments were performed. Factors associated with low serum zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
5
0
1
Order By: Relevance
“… 70 Serum Zn concentrations can be affected by various factors, including dietary intake; the status of Zn-binding proteins such as albumin, transferrin, and α-2-macroglobulin, diabetes mellitus, gastrointestinal disorders leading to malabsorption, heavy alcohol use, medications and various medical conditions that result in Zn depletion, and foods high in phytate content. 70 , 71 Noteworthy, the study by Vega-Cabello et al 42 included in this review reported that older adults with lower intake of high-phytate foods have a reduced risk of impaired lower extremity function and frailty compared with those with high intake even if their dietary Zn intake is similar. Nevertheless, available evidence also indicates that there is no clear relationship between serum Zn concentrations and Zn intake.…”
Section: Discussionmentioning
confidence: 97%
“… 70 Serum Zn concentrations can be affected by various factors, including dietary intake; the status of Zn-binding proteins such as albumin, transferrin, and α-2-macroglobulin, diabetes mellitus, gastrointestinal disorders leading to malabsorption, heavy alcohol use, medications and various medical conditions that result in Zn depletion, and foods high in phytate content. 70 , 71 Noteworthy, the study by Vega-Cabello et al 42 included in this review reported that older adults with lower intake of high-phytate foods have a reduced risk of impaired lower extremity function and frailty compared with those with high intake even if their dietary Zn intake is similar. Nevertheless, available evidence also indicates that there is no clear relationship between serum Zn concentrations and Zn intake.…”
Section: Discussionmentioning
confidence: 97%
“…Dyscholia of hepatic genesis, cholestasis and inflammation are the main factors in the formation of cholelithiasis in children. As a result of a genetic or acquired defect, the ratio of the main components of bile, which are synthesized in the liver, is disturbed -the liver produces lithogenic bile [19,20]. It has been proven that an elevated level of zinc plays a certain role in the formation of stones in the gallbladder, as it is known about its ability to activate crystallization processes in certain concentrations [21,22].…”
Section: рівень цинку в плазмі крові та перебіг жовчнокам'яної хвороб...mentioning
confidence: 99%
“…21,22 Furthermore, there is a great research interest in biology and biochemistry due to the toxicity of some heavy elements ( e.g. , Ni, Cd, Hg, Pb) 23 or their essential role in biochemical processes, as for Zn 24–26 and Se. 27–29…”
Section: Introductionmentioning
confidence: 99%
“…Heavy elements can play major roles in various application areas, including catalysis, [16][17][18] batteries, 19,20 and optoelectronics. 21,22 Furthermore, there is a great research interest in biology and biochemistry due to the toxicity of some heavy elements (e.g., Ni, Cd, Hg, Pb) 23 or their essential role in biochemical processes, as for Zn [24][25][26] and Se. [27][28][29] The most crucial relativistic effects originate from spin-orbit (SO) coupling and can be essential even for qualitative modeling of the heavy atom (HA) itself, 11,30,31 but also for the adjacent lighter atoms by the heavy atom on the light atom (HALA) effect.…”
Section: Introductionmentioning
confidence: 99%